Scenes of Uncertainty in Melville’s Battle-Pieces - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
After the chilly reception of his last major novel, The Confidence-Man and the failure to publish his volume of Poems in 1860, Melville probably acquiesced in the barrier between what his work had to offer and what the public was ready to receive. Yet the Civil War, the nation’s most serious crisis since it came into being, compelled him once again to reestablish the bond of artistic communication. Battle-Pieces, Melville’s only volume of poetry published with the intention of appealing to a national audience, would become an experimental attempt at articulating a collective experience, and, at the same time, reworking his own image of America within the ideational complexes of an increasingly pessimistic vision. The resulting work bears the mark of competing, although not wholly irreconcilable, commitments. The voice of the artist and thinker, whose disillusionment must have been further increased by the violence and irrationality of the Civil War, had to be brought into harmony with the public role ofthe poet speaking for the Union. Besides Whitman’s Drum-Taps, although much less acclaimed, Battle-Pieces remains the only considerable body of Civil War poetry by a canonical author who experienced the war as a contemporary. The poems in the volume reveal, on one hand, the genuine patriotism ofthe New Englander, and, on the other, admiration for the heroes and compassion for the victims on both sides. The volume finally fell short of success, and Melville’s artistic achievement is still largely considered as thwarted by what seems to be a certain clumsiness in craftsmanship: the unconventional stanzaic and rhyme patterns, the crooked syntax and an imagery frequently judged as clumsy and incongruous with the subject. However, the fact that Battle-Pieces succeeds Melville’s major fiction seems to be considerable justification to revise assumptions of artistic inadequacy. As occasional poetry about the Civil War, appealing first of all to a contemporary public, it failed to satisfy expectations about a clear-cut poetic and political stance, and most probably struck a dissonant note in a political climate where political and ideological values expected justification, and those committed to these values needed reassurance.